Viable and Effective Organizational Designs of Firms - Khandwalla, Pradip N. (Academy of Management Journal, 1973)
It is argued that ?uncertainty reduction,? ?differentiation,? and ?integration? should be positively associated. Not only are data on 79 manufacturing firms consistent with this argument, but when the sample is dichotomized in terms of profitability, the ?high? group exhibits positive association to a notably greater degree than the ?low? group.